On the origins of polarization holes in Bok globules - Brauer, Robert; Wolf, Sebastian; Reißl, Stefan (Astronomy and astrophysics, 2016)
Context. Polarimetric observations of Bok globules frequently show a decrease in the degree of polarization towards their central dense regions (polarization holes). This behaviour is usually explained with increased disalignment owing to high density and temperature, or insufficient angular resolution of a possibly complex magnetic field structure.Aims. We investigate whether a significant decrease in polarized emission of dense regions in Bok globules is possible under certain physical conditions. For instance, we evaluate the impact of optical depth effects and various properties of the dust phase.Methods. We use radiative transfer modelling to calculate the temperature structure of an analytical Bok globule model and simulate the polarized thermal emission of elongated dust grains. For the alignment of the dust grains, we consider a magnetic field and include radiative torque and internal alignment.Results. Besides the usual explanations, selected conditions of the temperature and density distribution, the dust phase and the magnetic field are also able to significantly decrease the polarized emission of dense regions in Bok globules. Taking submm/mm grains and typical column densities of existing Bok globules into consideration, the optical depth is high enough to decrease the degree of polarization by up to ΔP ~ 10%. If limited to the densest regions, dust grain growth to submm/mm size and accumulated graphite grains decrease the degree of polarization by up to ΔP ~ 10% and ΔP ~ 5%, respectively. However, the effect of the graphite grains occurs only if they do not align with the magnetic field.
Gesehen am 18.05.2020